2021
DOI: 10.1039/d1ta04981j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the electrocatalytic synthesis of 2,5-furandicarboxylic acid from 5-(hydroxymethyl)furfural

Abstract: Biomass conversion and biorefinery provide a feasible and novel way to release the increasingly serious energy crisis and environmental deterioration. 2,5-furandicarboxylic acid (FDCA) has received increasing attention as a significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 132 publications
0
85
0
Order By: Relevance
“…The past years have witnessed a great progress in the development of the BDAOR, with efficient carboxylic acid production being extensively reported [13, 14] . Successful cases include 5‐hydroxymethylfurfural (HMF) oxidation to 2,5‐furandicarboxylic acid (FDCA), [15 16] and glycerol oxidation to formic acid [4, 11] .…”
Section: Introductionmentioning
confidence: 99%
“…The past years have witnessed a great progress in the development of the BDAOR, with efficient carboxylic acid production being extensively reported [13, 14] . Successful cases include 5‐hydroxymethylfurfural (HMF) oxidation to 2,5‐furandicarboxylic acid (FDCA), [15 16] and glycerol oxidation to formic acid [4, 11] .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The past years have witnessed a great progress in the development of the BDAOR, with efficient carboxylic acid production being extensively reported. [13,14] Successful cases include 5-hydroxymethylfurfural (HMF) oxidation to 2,5furandicarboxylic acid (FDCA), [15 16] and glycerol oxidation to formic acid. [4,11] Currently, alkaline electrolyte is the most used medium for the BDAORs, as non-noble metal-based catalysts are generally active and durable in such electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic process is driven, through electron migration under mild conditions, by the electrochemical potential, thus eliminating the need for any external oxidant. [75] The development of HMF electrochemical oxidation is gaining increasing importance since it mainly needs non-noble metal catalysts at ambient temperature. Another important feature of this process, which makes it even more interesting from an environmental point of view, is the concomitant production of H 2 that occurs at the cathode during the HMF anodic oxidation according to the following process [Eqs.…”
Section: Electrochemical Oxidationmentioning
confidence: 99%
“…Indeed, homogeneous catalysts can get in close contact with the reactants, thus providing higher yields and better FE without any pH adjustment. [75] Choi et al [78] have reported that the use of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a mediator greatly reduced the overpotential requirements for HMF oxidation by suppressing water oxidation, obtaining a 98 % yield with more than 93 % of FE. However, a noble metallic electrode (Au) and excess TEMPO were used, causing a high cost of the process.…”
Section: Electrochemical Oxidationmentioning
confidence: 99%
See 1 more Smart Citation